First principle study of spintronic properties for double perovskites Ba2XMoO6 with X=V, Cr and Mn. (1st March 2016) - Souidi, A.; Bentata, S.; Benstaali, W.; Bouadjemi, B.; Abbad, A.; Lantri, T.
Abstract: Cubic double perovskites Ba2 XMoO6 (X=V, Cr and Mn) compounds are studied using the full potential linearized augmented plane wave (FP-LAPW) method within the frame work of density functional theory (DFT). The structural, electronic and magnetic properties are calculated by using the Generalized Gradient Approximation (GGA), GGA+U and modified Becke–Johnson mBJ-GGA. Density of States and band structure results reveal a similar half-metallic ferromagnetic ground state for Ba2 CrMoO6 . Whereas, a metallic ferromagnetic character is predicted for Ba2 VMoO6 and a matching metallic ferromagnetic ground state is obtained for Ba2 MnMoO6 . The mBJ calculations yield a better energy-gap than the GGA and GGA+ U methods.